New records of benthic marine algae from Morocco (eastern Atlantic Ocean): morphology, taxonomy and distribution - Hassoun, Mustapha; Moussa, Hanaa; Salhi, Ghizlane; Zbakh, Hanaa; Riadi, Hassane; Kazzaz, Mohamed (Acta Botanica Malacitana, 2018)
Abstract We report new records and corological data for three Moroccan marine macroalgae that complete their distribution information. Radicilingua thysanorhizans is new record for Morocco; Champia compressa is recorded for the first time from the eastern coast of the Atlantic Ocean. Diplothamnion jolyi is widely distributed in the western coast of the Atlantic coast and Pacific Islands, and recently reported from the Mediterranean Sea; this new record from Moroccan Atlantic coast extends their distribution range. Key words: Algae, Atlantic Ocean, Champia compressa, Diplothamnion jolyi, Radicilingua thysanorhizans. Resumen Se aportan nuevos registros y datos corológicos para tres macroalgas marinas de Marruecos, que completan la información sobre su distribución. Radicilingua thysanorhizans es cita nueva para Marruecos. Champia compressa se registra por la primera vez en la costa oriental del Océano Atlántico. Diplothamnion jolyi se distribuye ampliamente en la costa occidental de la costa atlántica y las islas del Pacífico y ha sido recientemente citada en el mar Mediterráneo; esta nueva cita para costa Atlántica Marroquí amplia su rango de distribución. Palabras clave: Algae, Océano Atlántico, Champia compressa, Diplothamnion jolyi, Radicilingua thysanorhizans.